Cultural Forests in Cross Section: Clear-Cuts Reveal 1, 100 Years of Bark Harvesting on Vancouver Island, British Columbia. Issue 3 (July 2019) - Earnshaw, Jacob K.
Abstract : Culturally modified trees (CMTs) provide tangible evidence of long-term forest use by Indigenous peoples. In Northwest Coast cedar forests, this record rarely spans beyond the last three centuries because older bark-harvest scars have been obscured through taphonomic processes such as natural healing and decay. Thus, archaeological visibility and identification are hindered. Here, I recover chronologies of ancient forest harvesting using a post-impact assessment methodology of targeting old-growth clear-cuts in southern Nuu-chah-nulth territories on the west coast of Vancouver Island, British Columbia, Canada. Bark-peeling scars are identified and dated in cross section by growth-ring patterns of recently logged trees. Approximately half of all bark-peeling scars are "embedded" inside healing lobes, suggesting at least half of all such CMTs are effectively invisible in standing forests. Features in these post-impact surveys predated those discovered in conventional archaeological impact assessments by a mean of almost a century. Additionally, one of the oldest continually used cultural forests ever recorded, dating to AD 908, is found in the Toquaht Nation traditional territory. These findings uncover measurable frequencies of cedar-bark harvesting generations prior to the contact period and reveal the inadequacy of heritage protections for old-growth cedar stands. Abstract : Los árboles culturalmente modificados (CMTs por sus siglas en inglés) proporcionan evidencia tangible del uso a largo plazo del cedro por parte de los pueblos Indígenas. En el noroeste del Pacífico, este registro rara vez se extiende más allá de los últimos tres siglos o la duración de vida potencial de los bosques circundantes. Se ha pensado que las cicatrices culturales más antiguas en el cedro están ocultas a través de procesos de curación natural o deterioro a lo largo del tiempo, lo cual impide su identificación. Aquí recupero cronologías de usos antiguos de bosques a través de las "evaluaciones post-impacto" de recientes recortes claros de bosque de viejo crecimiento en el sur de los territorios de Nuu-chah-nulth en la costa oeste de la Isla de Vancouver, Columbia Británica, Canadá. Las cicatrices de peladura de la corteza se identifican y datan en sección transversal según el patrón de crecimiento del anillo dentro de los árboles recientemente talados. Encuentro que la mitad de todas las cicatrices de peladura de la corteza de los cedros están "incrustadas" dentro de lóbulos de curación e invisibles dentro de un bosque en pie. Se encontró que las características de estas evaluaciones post-impacto son anteriores, en promedio, a las descubiertas en las evaluaciones de impacto arqueológico (AIAs por sus siglas en inglés) convencionales de casi un siglo. Uno de los bosques culturales de uso continuo más antiguo jamás registrado, que data de 908 dC, se encuentra en la Primera Nación Toquaht. Los hallazgos descubren frecuencias medibles de las actividades humanas generaciones anteriores al período de contacto y revelan la insuficiencia de las protecciones del patrimonio regional para las masas de cedro de viejo crecimiento.